2009
DOI: 10.12968/ijpn.2009.15.7.43422
|View full text |Cite
|
Sign up to set email alerts
|

Developing meaningful learning experiences in palliative care nursing education

Abstract: To help nurses develop effective clinical decision-making skills, it is essential that palliative care education includes opportunities for undergraduate and practicing nurses to develop cognitive skills in addressing real-life clinical problems. This article describes the learning experiences within an elective nursing course designed to strengthen the clinical decision-making skills of students in the context of palliative care and interprofessional practice. A description of the course context, major learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…She argues that nursing students exposed to death without appropriate education develop anxiety and negative attitudes and eventually limit their involvement in the care of dying patients. While Quint's work subsequently encouraged the inclusion of death education in curricula, more recent concerns focus on the amount of death education and nurses' preparedness to care for dying patients [31,32]. Allchin [22], thus, comments that nurse educators for more than thirty years have been calling for a greater emphasis in nurse education on the topics of death and dying, with this lack reflected in the quality of care provided [20, page 305].…”
Section: Introductionmentioning
confidence: 99%
“…She argues that nursing students exposed to death without appropriate education develop anxiety and negative attitudes and eventually limit their involvement in the care of dying patients. While Quint's work subsequently encouraged the inclusion of death education in curricula, more recent concerns focus on the amount of death education and nurses' preparedness to care for dying patients [31,32]. Allchin [22], thus, comments that nurse educators for more than thirty years have been calling for a greater emphasis in nurse education on the topics of death and dying, with this lack reflected in the quality of care provided [20, page 305].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, despite an increasing awareness and inclusion of death education in pre-registration curricula (see Dickinson et al, 2008), there is evidence to suggest persistent shortcomings in the nursing profession's ability to meet the needs of dying patients. Allchin (2006) thus comments that nurse educators for more than thirty years have been calling for a greater emphasis in nurse training on EOL care, with this lack of education reflected in the quality of EOL care provided to patients (Brajtman et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that undergraduate nursing students' palliative care learning needs are best addressed through a multifaceted approach (Brajtman, Higuchi, & Murray, 2009). Palliative care content has the greatest effects on nurses when it is conducted over several weeks, involves a mix of didactical methods and facilitates the exploration of multiple themes which are integrated with practical experiences and then reflected upon (Adriaansen & van Achterberg, 2008).…”
Section: Discussionmentioning
confidence: 99%